2020
DOI: 10.1038/s41598-020-73789-4
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation increases levels of osteocalcin and uncarboxylated osteocalcin in human sera

Abstract: Smoking is thought to be a risk factor for osteoporosis development; however, the consequences of stopping smoking for bone homeostasis remain unknown. Here we conducted two separate human studies and show that bone mineral density was significantly lower in smokers than in non-smokers. The first was an observational study of pre- and post-menopausal healthy female smokers and non-smokers; the second included 139 current smokers determined to stop smoking. In the second study, levels of bone formation markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Alcohol is metabolized to acetaldehyde, which inhibits osteoblasts. 19 However, despite there being a significant difference in the proportion of alcohol drinkers in the fracture group than in the non-fracture group in univariate analysis, this was not significant in multivariate analysis. This could be because we did not measure the amount of alcohol consumed.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Alcohol is metabolized to acetaldehyde, which inhibits osteoblasts. 19 However, despite there being a significant difference in the proportion of alcohol drinkers in the fracture group than in the non-fracture group in univariate analysis, this was not significant in multivariate analysis. This could be because we did not measure the amount of alcohol consumed.…”
Section: Discussionmentioning
confidence: 85%
“…Therefore, if a patient’s family member is a smoker, they too should be advised to stop smoking. Kiyota et al 19 confirmed that the disruption of bone homeostasis induced by smoking could recover gradually after smoking cessation. Therefore, stopping smoking postoperatively will help prevent the occurrence of new fractures.…”
Section: Discussionmentioning
confidence: 95%
“…We investigated the influence of tobacco smoking and alcohol consumption on the development of osteoporosis by analyzing the data collected by the TWB because these influences were unclear in previous research [23][24][25][26] . First, we found the participants in the smokingonly group and both smoking and drinking group to be at a higher risk of developing osteoporosis than those in the non-smoking and non-drinking groups.…”
Section: Discussionmentioning
confidence: 99%
“…In postmenopausal women, bone mineral density was significantly lower in smokers than in non-smokers in a human clinical study. An additional animal study showed that administration of nicotine to wild-type mice decreased bone mass ( Kiyota et al, 2020 ).…”
Section: Non-communicable Diseases Caused By Smoking: Dysregulation O...mentioning
confidence: 99%
“…Also, chronic overstimulation of the RAAS is thought to result in lower vitamin D levels ( Ferder et al, 2013 ). Smoking cessation was associated with a significant increase in bone mineral density within a short period of time in a human clinical trial and in an animal study, as reflected by a significant decrease in serum levels of TRAP5b, a marker of bone resorption, and an increase in levels of osteocalcin and non-carboxylated osteocalcin ( Kiyota et al, 2020 ).…”
Section: Non-communicable Diseases Caused By Smoking: Dysregulation O...mentioning
confidence: 99%